Penerapan Discovery Learning Untuk Meningkatkan Berpikir Kritis Dan Hasil Belajar Kimia Mahasiswa - Siregar, Fitri Handayani (Journal of Engineering and Information Technology for Community Service, 2024)
This study aims to improve critical thinking skills and chemistry learning outcomes through the Discovery Learning model. This research was conducted at the Health Analyst Study Program of YRSU Dr. Rusdi Health Polytechnic. The subjects amounted to 29 students. This type of research is a class action research consisting of planning, action implementation, observation and reflection using the Discovery Learning learning model. Tests were used to measure students' initial abilities and learning outcomes, and observation sheets were used to measure students' critical thinking skills. Learning using the Discovery Learning model proved effective in improving student learning outcomes and critical thinking skills. The success of the application in improving student learning outcomes is indicated by changes in the process of cycle I, the increase in class average scores after the action from the pretest of 85.70% rose to 89.70% at the time of the posttest. The increase in the number of students who reached the KKM score was 17.24%. In cycle II, success was indicated by an increase in the class average score after the action from the pretest of 62.1% to 79.3% at the time of the posttest. The increase in the number of students who reached the KKM score was 6.8%. Based on the analysis of students' critical thinking skills, the successful application in improving students' critical thinking skills is still categorized as Very Good.